Sistem Informasi Pemasaran Berbasis Website dalam Meningkatkan Pembelian Kerajinan Anyaman di Cv Binangkit Kabupaten Tasikmalaya - Sri Sudiarti (Entrepreneurship Faculty, Universitas Garut, 2019)
The purpose of this study was to determine the effectiveness of marketing information system at CV Binangkit in Tasikmalaya Regency and to find out the use of the website as a marketing medium to increase the purchase of netting crafts at CV. Binangkit in Tasikmalaya Regency. The research method used was quantitative descriptive survey approach. The sample of this study were 75 respondents. Statistical analysis was done through simple regression analysis. The results of the analysis indicated that the Marketing Information System had a positive effect on purchasing decisions. A good marketing information system can influence the purchasing decision. It is expected that Website-based marketing information system can be developed to improve public purchasing decisions. CV Binangkit is also suggested to provide more information about their products by regularly updating their products and making more promos on their website so that consumers will be more interested in buying their products.